“I just thought I was lucky to be protected from HIV:” Qualitative evaluation of barriers and facilitators of pre-exposure prophylaxis use for adolescent girls and young women at higher risk of HIV acquisition in Lilongwe, Malawi - Mallory Michalak; Odala Sande; Sam Phiri; Hannock Tweya; Geldert Chiwaya; Joseph Chintedza; Beatrice Matanje; Christine Kiruthu-Kamamia; Jacqueline Huwa; Jane Chiwoko; Tom Chaweza; Rose Nyirenda; et al. (PLoS ONE, 2025)
Adolescent girls and young women (AGYW) are at higher risk of HIV acquisition than their male counterparts, especially in sub-Saharan African countries such as Malawi. Therefore, HIV prevention programming is a key component to reducing this risk. We conducted a formative qualitative assessment with AGYW and their health providers to understand AGYW’s perceptions of their own HIV risk, self-efficacy to protect themselves, and the implications of these factors on pre-exposure prophylaxis (PrEP) use. Our study found that AGYW are aware and interested in using PrEP, which can allow choices that protect their sexual health and well-being. Innovative service delivery models that minimize stigma and offer other reproductive health services such as contraception are needed to provide comprehensive care. Additionally, AGYW and their health providers would benefit from education about HIV risk perception and PrEP effectiveness to improve use of PrEP. Robust AGYW PrEP service delivery, including new biomedical prevention strategies, may facilitate efforts to achieve epidemic control.